Biometry of the Heart and its Vessels in Young and Adult of Local Non-Descript Goats (Capra hircus) of Vidarbha Region - Sathapathy, S.; Khandate, S. P.; Dalvi, R. V.; Charjan, R. Y.; Salankar, A. M. (Indian Journal of Veterinary Anatomy, 2013)
The present biometrical study was conducted on the heart and its vessels of six local non-descript male and female young (1-2 years) and adult (2-3 years) goats. Morphometric data indicated that the values were generally higher in females as compared to males in young and adult goats except for some dimensions. Moreover, the values for adults were greater than the young goats. The baseline data evolved may be useful to the veterinarians in forensic cases.